Effectiveness of Multimedia Learning Package on the Science Achievement: Exploring the Impact of Multimedia Learning Package on Science Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Multimedia Technology has paved the new avenues for implementation of instructional and educational ideas. It presents information in an effective way and offers an opportunity to students to structure and learn exercise at their own pace. The idea of multimedia innovation is wide and it has limitless utilization fields it is a significant component as an educational innovation notwithstanding its utilization in medicinal and statistical areas and in setting up databases. In this study the focus is on the types and benefits of multimedia, evolution of multimedia and multimedia instructional packages in education and Scope of Multimedia Resources and Instructional Packages in Science Education.